Behaviour of tie confined reinforced concrete columns subjected to standard fire exposure - Buch, Shujaat Hussain; Sharma, Umesh Kumar (Advances in structural engineering, 2025)
The fire resistance of Reinforced Concrete (RC) Columns, defined as the duration for which the columns can withstand fire exposure without losing structural integrity, is influenced by confining parameters such as cross ties, tie anchorage, and tie spacing. This paper evaluates the influence of various confining parameters, including tie reinforcement diameter and diamond tie configuration. Additionally, the study determines the optimized configuration of cross ties and tie spacing for assessing the fire resistance of RC Columns. These parameters are examined under two spalling scenarios: normal and explosive. Nine full-scale RC columns, cast at two concrete grades, are experimentally tested to determine fire resistance. It is found that fire resistance increases by 49% when tie confinement is improved in normal-strength concrete columns and by 149% when tie confinement is improved in high-strength concrete columns. Numerical simulation is conducted to determine the level of confinement indicated by the moment-curvature behavior of columns. 3D solid element models are sequentially analyzed to assess the fire performance of column sections, and parametric analysis is performed.